The Frequency and Clinical Associations of Interatrial Block among Patients with Heart Failure - Altunbaş, Gökhan (European Journal of Therapeutics, 2023)
Objective: Heart failure is a rising global pandemic. Numerous structural and functional alterations occur within the heart in response to reduced ejection fraction and dilated chambers. The frequency and clinical associates of interatrial block (IAB) amongheart failure patients with reduced systolic function were evaluated in this study. Methods: Patients with heart failure and reduced systolic function (ejection fraction [EF] <50%) were consecutively enrolled in the study. Patients with atrial fibrillation were excluded. In total, 142 patients with sinus rhythm and systolic heart failure were included. Demographic variables and basic echocardiographic variables were recorded. The presence, absence, and degree of IAB were recorded using standard twelve-lead electrocardiography (ECG). A p wave duration of <120 ms was accepted as normal interatrial conduction. If the p-wave duration was ≥120 ms and p-wave morphology was normal in inferior derivations, it was accepted as partial IAB. A combination of a prolonged p-wave duration (≥120 ms) and biphasic p waves (positive and negative) was accepted as advanced IAB. The Kruskal–Wallis test was used to compare the variables and IAB. Results: In total, 142 patients had heart failure (EF <50%) and sinus rhythm; 79 patients (59%) had normal interatrial conduction, 37 (27.6%) had partial IAB, and 18 (13.4%) had advanced IAB. The total frequency of IAB among patients with heart failure was 38.7%. The presence and degree of IAB were associated with advanced age (p=0.004) but not with the etiology of heart failure (ischemic and nonischemic) and gender of the patients. Also, the degree of systolic impairment, as assessed by EF, was not associated with the degree of IAB (p=0.19). The ECG P-wave duration had a significant correlation with age (p=0.002) and left atrial diameter (p=0.048). Conclusion: Interatrial block is quite common and independent of the degree of systolic impairment among patients with heart failure. Since the clinical implication is high, frequent monitoring and a close follow-up is necessary in these patients.